2020
DOI: 10.1021/acs.iecr.0c01275
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Hierarchical Silicalite-1 Zeolite Encapsulated PtNi Bimetals for Selective Hydroconversion of Methyl Stearate into Aviation Fuel Range Alkanes

Abstract: Hollow hierarchical silicalite-1 zeolite encapsulated Pt and PtNi bimetals (Pt@HS-1 and PtNi@HS-1) were successfully synthesized via a ship-in-bottle strategy and employed for hydroconversion of methyl stearate into aviation fuel range alkanes in a fixed-bed reactor. Their morphologies, texture, and acidity were characterized by field-emission scanning electron microscopy, field-emission transmission electron microscopy, X-ray diffraction, nitrogen adsorption and desorption, hydrogen temperature-programmed red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 74 publications
1
26
0
Order By: Relevance
“…XPS measurements were implemented to analyze the surface components and their chemical states of the prepared catalysts (Figure 1C and Figure S8). As listed in Table S4, the investigation based on Co content obtained from XPS and XRF analysis (XPS/XRF) indicates the Co species are successfully encapsulated within the zeolite for Co‐acac@S‐1 and Co‐edta@S‐1, while a substantial of Co species locate on the external surface of zeolite for Co/S‐1 catalyst 25 . The core‐level binding energies (BEs) of Co 2p 3/2 peak of Co‐acac@S‐1 and Co‐edta@S‐1 catalysts are, respectively, located at 782.6 eV and 782.9 eV, which is ascribed to Co 2+ species 9 (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…XPS measurements were implemented to analyze the surface components and their chemical states of the prepared catalysts (Figure 1C and Figure S8). As listed in Table S4, the investigation based on Co content obtained from XPS and XRF analysis (XPS/XRF) indicates the Co species are successfully encapsulated within the zeolite for Co‐acac@S‐1 and Co‐edta@S‐1, while a substantial of Co species locate on the external surface of zeolite for Co/S‐1 catalyst 25 . The core‐level binding energies (BEs) of Co 2p 3/2 peak of Co‐acac@S‐1 and Co‐edta@S‐1 catalysts are, respectively, located at 782.6 eV and 782.9 eV, which is ascribed to Co 2+ species 9 (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…The best bi-functional zeolite-based catalysts for approaching the composition of oils to aviation fuel will be the ones containing transition metals that provide hydroprocessing which includes hydrodeoxygenation, hydrocracking, hydrogenation and hydroisomerization. Previous studies indicated that zeolite-supported noble metal catalysts have incomparable performance owing to the combining of superior hydrodeoxygenation ability of noble metals with the tunable acidity of zeolite supports ( Snåre et al, 2006 ; Philippaerts et al, 2011 ; Sotelo-Boyás et al, 2011 ; Van Aelst et al, 2016 ; Yang and Carreon, 2017 ; Crawford and Carreon, 2018 ; Niu et al, 2020 ). This section considers the main processes of NOF and utilization by-product of the biodiesel industry, for which zeolite-based catalysts can be successfully used.…”
Section: Catalytic Processes With Transition Metals On Zeolitesmentioning
confidence: 99%
“…Ni is a well-known catalyst for hydrotreatment, in addition, it has a strong capacity to cleave C-C bonds. The combination of the catalytic properties of Ni and zeolite opens up interesting prospects for biofuel production and is currently being actively studied ( Niu et al, 2020 ). Ni NPs supported on hierarchical meso-Y ( Cheng et al, 2019a ), sulfonated meso-Y ( Cheng et al, 2019b ), and desilicated meso-Y ( Zhang Z. et al, 2019 ) were applied for hydrocracking conversion of microalgal oil to jet fuel range hydrocarbons and the reaction parameters were optimized to achieve iso-alkanes.…”
Section: Catalytic Processes With Transition Metals On Zeolitesmentioning
confidence: 99%
“…Another crucial factor determining the hydrodeoxygenation activity of the catalysts is the choice of the support. A variety of supports has been studied in the literature for the selective deoxygenation of fatty compounds. The exploitation of minerals as “natural” catalysts or catalytic supports is very important in the context of sustainable development and the cyclic economy. …”
Section: Introductionmentioning
confidence: 99%
“…Its chemical composition is (Ca,Na 2 ,K 2 )­Al 2 Si 10 O 24 ·7H 2 O. Mordenite is a zeolite material composed of bound SiO 4 and AlO 4 tetrahedra forming two types of cross-linked micropores with apertures 0.67 nm × 0.7 nm and 0.34 nm × 0.48 nm . Zeolites are commonly used as supports of Ni catalysts for relevant reactions. Thus, Ni catalysts supported on natural mordenite seems to be a promising approach for developing suitable catalysts for selective deoxygenation of fatty compounds. The acidity of this zeolite support is expected to accelerate the hydrodeoxygenation of fatty alcohols (intermediate products of SDO) producing hydrocarbons with the same number of carbon atoms and water.…”
Section: Introductionmentioning
confidence: 99%